Analysis Of Liquidity, Profitability, And Solvency Ratio for Measuring Business Operations in Food, Beverage and Tobacco Companies Listed on The Indonesian Stock Exchange Period 2015-2019 - Lestari, Melina Budi; Sari, Silvia Waning Hiyun Puspita; Syah, Toufan Aldian (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
This study aims to see how the development financial performance of a food, beverage, and cigarette company listed on the Indonesia Stock Exchange in 2015-2019 using the financial ratio analysis method, namely the liquidity ratio, profitability, and solvency. The financial ratios used are the Current Ratio (CR), Quick Ratio (QR), Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Debt to Assets Ratio (DAR). Research result shows that, in general, the financial ratios of food, beverage, and cigarette companies listed on the Indonesia Stock Exchange have fluctuated. However, some of them have. Some companies that have good financial ratios can also see bad ones, how good or bad the company's financial performance is.